Tumor-associated macrophages promote bladder cancer metastasis through the CCL20-CCR6 axis - Ryunosuke Nakagawa; Kouji Izumi; Kaoru Hiratsuka; Takahiro Inaba; Yoshiki Koketsu; Ren Toriumi; Shuhei Aoyama; Taiki Kamijima; Hiroshi Kano; Tomoyuki Makino; Renato Naito; Suguru Kadomoto; et al. (Neoplasia: An International Journal for Oncology Research)
We investigated the mechanisms of interaction between bladder cancer (BC) cells and tumor-associated macrophages (TAMs). Coculturing BC cell lines (UMUC3 and T24) with macrophage-like cells differentiated from THP-1 into M2-like TAMs revealed a decrease in Cluster of Differentiation (CD) 68 expression and an increase in CD206 expression. This differentiation enhanced BC cell migration and invasion. Additionally, M2-like TAMs significantly increased the secretion of C–C motif chemokine ligand (CCL) 20, which promotes BC cell migration and invasion via the MEK/ERK signaling pathway through its paracrine effects. Coculturing with TAMs also elevated the expression of CC chemokine receptor (CCR) 6 in BC cells, indicating increased sensitivity to CCL20. Immunohistochemistry analysis of human BC tissues showed a significant correlation between CCR6 expression levels and BC prognosis. Inhibition of CCR6 reduced BC cell metastasis both in vitro and in vivo. Additionally, CXCL1 secretion from BC cells was found to contribute to the M2-like polarization of macrophages and to enhance BC cell migration and invasion through autocrine and indirect effects. In summary, CCL20 and CXCL1 play crucial roles in the interaction between BC cells and TAMs.